Development of Canva-Assisted Math Learning Videos at SMPN 2 Lolak - Wowor, Yohanes Fandy Putra William; Abbas, Nurhayati; Uno, Hamzah (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
This study aims to produce a Canva-assisted mathematics learning video product that is valid, practical and effective in learning. This development research was carried out at SMP Negeri 2 Lolak which focused on learning mathematics videos assisted by Canva data presentation materials. This research has been carried out based on the instructional media development procedure referring to the ADDIE development stage which consists of five stages of development namely (1) analysis (analyze), (2) design (design), (3) development (development), (4) Implementation (implement), (5) evaluation (evaluate). The results of the development of Canva-assisted mathematics learning videos using the ADDIE model are based on the validation of learning videos by 2 material and media experts. The total score obtained from media experts is 68 points with a percentage of 94.44% (appropriate) and the total score from material experts is 56 points with a percentage of 93.33% (appropriate). The results of the validation of the small group student response questionnaire on the practicality of the media obtained a total score of 94 points with a percentage of 78.33% (practical) and a large group score of 692 points with a percentage of 86.50% (very practical). Then for student learning outcomes at the time of pretest and posttest there was an increase in the number of student learning outcomes at the time of pretest, the total value of 1100 increased to 1655 at the time of posttest. There was an increase of 555 points. Second, there was an increase in the average value of student learning outcomes at the pretest with an average score of 55 (55%) increasing to 82.75 (83%) at the posttest. There was an increase of 27.75 points (28%). The results showed that the Canva-assisted mathematics learning video on the data presentation material obtained an average interpretation of the appropriate assessment and obtained the appropriate (valid) decision results. From the steps that have been carried out, it can be concluded that the mathematics learning videos assisted by Canva data presentation materials are valid, practical and effective to use.